On the structural and optoelectronic properties of chemically modified oligothiophenes with electron-withdrawing substituents for organic solar cell applications: A DFT=TDDFT study - Franco, Francisco C., Jr. (Animo Repository, 2017)
Solar cells based on conjugated polymers have been gaining attention in the recent decades due to its various potential advantages. In this study, several oligothiophene derivatives based on poly(3-hexylthiophene-2,5-diyl) (P3HT) were investigated by performing density functional and time-dependent density functional theory based calculations. The structural properties of various oligothiophenes substituted with electron-withdrawing groups (F, Cl, CN, NO2, COCH3) in its bithiophene monomer exhibited planar and non-planar structures. These structural properties depend on the interaction of the substituent and the surrounding molecules of the oligothiophenes. It is observed that the oligothiophenes with planar structures have decreased EGap while those with non-planar structures have increased EGap. Also, the effect of substitution on the frontier orbital energies was explored and it is observed that F, Cl, and CNsubstituted derivatives decrease in ELUMO more than EHOMO resulting to smaller EGap. These changes in EGap are attributed to the induced structural and electronic changes in the oligothiophenes by the substituents. Furthermore, other properties (exciton binding energy, ionization potential, and open-circuit voltage) relevant to organic solar cells were investigated. It was found that cyano substituted P3HT is a good polymer blend candidate for organic solar cells. In general, this study shows how the optoelectronic properties of P3HT could be significantly improved via electron with drawing substitutions for solar cell applications. © 2017 The Physical Society of Japan.